Investing in Adolescent Girls’ Nutrition in Bangladesh : Situation Analysis of Trends and Ways Forward - Mridha, Malay Kanti; Hossain, Mokbul; Hassan, Tanvir; Sutradhar, Ipsita; Bente Kamal, Samiun Nazrin; Khan, Akib; Ahmed, Nizam Uddin; Khondker, Rudaba; Mustaphi, Piyali; Chowdhury, Ireen A; Adams, Alayne M.; Hyder, Ziauddin (World Bank, Washington, DC, 2019)
Adolescents are among the age groups most vulnerable to malnutrition and their situation requires priority attention. However, information on adolescent nutrition in Bangladesh is limited. Using data from the Food Security and Nutrition Surveillance Project (FSNSP), we examined the nutritional situation of adolescent girls including regional and urban-rural patterns in undernutrition and overnutrition, dietary diversity, household food security, and as well as their growth dynamics. Our analysis focused on data collected from 2012 to 2014. The total sample size was 15,740 adolescent girls aged 10–19 years, of which one third were early adolescents aged 10–14 years, and one-tenth lived in urban areas. The authors found that among young adolescent girls, the proportion of moderate to severe thinness declined from 35 percent to 28 percent between 2012 and 2014, and rates of overweight and obesity were consistently low. For older adolescent girls (ages 15-19), the proportion of moderate to severe thinness remained low, while rates of overweight and obesity increased from 13 percent to 23 percent between 2012 and 2014. Overall, 17 percent of younger adolescent girls were stunted in 2012, decreasing to 11 percent in 2014. Study findings also highlighted substantial regional variations in both age groups. Of concern was a decrease in dietary diversity. The proportion of younger adolescent girls falling into the poor dietary diversity group increased from 54 percent in 2012 to 60 percent in 2014, and for older adolescent girls, a similar pattern was evident, with rates increasing from 53 percent to 64 percent. The analysis of growth dynamics indicated substantial deficits relative to healthy norms in the younger adolescent period. Study findings emphasize the importance of leveraging critical developmental entry points through high impact adolescent nutrition interventions. These investments will help ensure a future healthy work force, and a healthy next generation of children in Bangladesh.